Les revistes bilingües a la Tortosa de la II República. - GOMBAU DOMINGO, M. CARME (Scripta, 2016)
There were two linguistic actitudes in the tortosine press of the first third in the 20th century: the fabriana amb the tortosinista. The fabriana, in favour of the IEC linguistic model, was in minority during the 20's, but it became widespread from the 30's (La Veu de Tortosa, La Veu Comarcal, Ara, Acció, Vida Tortosina i Lluita). The second, the tortosinista, had a local ideology and compared the tortosinisme talk as a complet language, but it was reduced during the n Republic to three magazines: La Zuda, Germanor i La Santa Cinta.